A Network-Based Stochastic Epidemic Simulator: Controlling COVID-19 With Region-Specific Policies - Huseyin Atakan Varol; Michael Lewis; Mukhamet Nurpeiissov; Almas Mirzakhmetov; Bauyrzhan Ibragimov; Aknur Karabay; Daulet Baimukashev; Askat Kuzdeuov; Askat Kuzdeuov (IEEE, 2020)
Open-source simulator modeling a country as a network of regions; each node runs SEIR with inter-node mobility. Incorporates demographics, mobility, and resource capacity for policy evaluation.
Keywords: open access; regional policies; network simulation; SEIR; COVID-19; stochastic epidemic modeling; stochastic epidemic modeling